A Modified Newmark Methodology for Permanent Deformation Analysis of Rock-Fill Dams. (1st April 2018) - Li, Hongjun; Zhong, Hong; Yan, Zuwen; Zhao, Jianming
Abstract : Newmark sliding block approach has been extensively studied by many researchers in the past decades. Significant progress has been made to alleviate its deficiencies and overcome its simplifying assumptions, but some aspects such as the cyclic shear strength and time history vertical acceleration in the Newmark sliding displacement analysis are seldom considered strictly. In the presented research, a modified Newmark methodology for sliding deformation analysis of rock-fill dams subjected to strong earthquake is proposed. In order to make the seismic safety evaluation of dams more realistic, the influence of cyclic shear strength (earthquake-induced reduction of shear strength) and time history vertical acceleration obtained from the dynamic response analysis on the critical acceleration and accumulative sliding displacement of the flexible sliding body is considered. Detailed comparison between the proposed method and existing methods is performed via the analysis of two typical dams, that is, a virtual rock-fill dam with a height of 100 m which is assumed to be situated on rock formation and a real core rock-fill dam with a height of 150 m built on deep overburden layers. It is demonstrated that the cyclic shear strength and time history vertical acceleration within flexible sliding body, as highlighted in the proposed method, have significant effect on the seismic safety evaluation, critical acceleration, and accumulation of sliding deformation of rock-fill dams subjected to strong earthquake loading. The existing approaches tend to provide unconservative evaluation on the consequences of earthquakes on rock-fill dams.